News Shocks and Optimal Simple Rules - Hans-Werner Wohltmann; Roland C. Winkler (Verein für Socialpolitik, 2010)
This paper evaluates the performance of optimal simple policy rules in the presence of news shocks. It is shown that the inclusion of forward-looking elements enhances the performance of simple optimized interest rate rules when agents learn about future disturbances in advance. We provide a rationale for this result by demonstrating that, if shocks are news shocks, the optimal unrestricted control rule under commitment contains as a basic principle a forward-looking element.
Keywords: E32; E52; E58; 330; News Shocks; Optimal Simple Rules; Optimal Monetary Policy